Cognitive changes and neural correlates after oral rehabilitation procedures in older adults: a protocol for an interventional study - Linn Hedberg; Urban Ekman; Love Engström Nordin; Jan-Ivan Smedberg; Pia Skott; Åke Seiger; Gunilla Sandborgh-Englund; Eric Westman; Abhishek Kumar; Mats Trulsson (BMC, 2021)
Abstract Background Epidemiological studies show an association between masticatory function and cognitive impairment. This has further strengthened the notion that tooth loss and impaired masticatory function may be risk factors for dementia and cognitive decline. Animal experiments have indicated a causal relationship and several possible mechanisms have been discussed. This evidence is, however, lacking in humans. Therefore, in the current interventional study, we aim to investigate the effect of rehabilitation of masticatory function on cognition in older adults. Methods Eighty patients indicated for prosthodontic rehabilitation will be randomly assigned to an experimental or a control group. Participants will conduct neuropsychological assessments, masticatory performance tests, saliva tests, optional magnetic resonance imaging, and answer questionnaires on oral health impact profiles and hospital anxiety and depression scale before, 3 months, and 1 year after oral rehabilitation. The difference between the two groups is that the control group will be tested an additional time, (at an interval of about 3 months) before the onset of the oral rehabilitation procedure. The primary outcome is a change in measures of episodic memory performance. Discussion Although tooth loss and masticatory function are widespread in older people, it is still an underexplored modifiable risk factor potentially contributing to the development of cognitive impairment. If rehabilitation of masticatory function shows positive effects on the neurocognitive function, this will have great implications on future health care for patients with impaired masticatory status. The present project may provide a new avenue for the prevention of cognitive decline in older individuals. Trial registration: The protocol for the study was retrospectively registered in ClinicalTrials.gov Identifier: NCT04458207, dated 02-07-2020.